2019
DOI: 10.1177/0022034519866628
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Factors Explain Socioeconomic Inequalities in Children’s Dental Caries

Abstract: The aim of this article was to quantify socioeconomic inequalities in dental caries experience among Australian children and to identify factors that explain area-level socioeconomic inequalities in children’s dental caries. We used data from the National Child Oral Health Survey conducted in Australia between 2012 and 2014 ( n = 24,664). Absolute and relative indices of socioeconomic inequalities in the dental caries experience in primary and permanent dentition (decayed, missing, and filled surfaces [dmfs] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 28 publications
3
31
0
1
Order By: Relevance
“…of families in the present study sought help from a dentist for treatment compared with only 7.8% who sought help for prevention. An Australian study has reported that dental visits actually contribute 30.3% to the explanation of inequalities in ECC [16]. This result indicates that our awareness of prevention is still insubstantial and that the purpose of dental visits is incorrectly implemented as more for treatment and rarely for prevention.…”
Section: Logistic Regression Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…of families in the present study sought help from a dentist for treatment compared with only 7.8% who sought help for prevention. An Australian study has reported that dental visits actually contribute 30.3% to the explanation of inequalities in ECC [16]. This result indicates that our awareness of prevention is still insubstantial and that the purpose of dental visits is incorrectly implemented as more for treatment and rarely for prevention.…”
Section: Logistic Regression Analysesmentioning
confidence: 99%
“…At present, many high-risk factors associated with dental caries have been demonstrated, such as poverty, race, eating habits, family economic status, education level, etc. [14][15][16]. However, few studies have separately analysed and assessed the risk factors for each age group; instead, they have considered all preschool children as a whole, which has hindered us from preventing dental caries more effectively by optimizing and enriching OHE.…”
Section: Introductionmentioning
confidence: 99%
“…prevention. An Australian study reported that dental visit actually contributes 30.3% in explaining inequalities in ECC [15]. This indicates that our awareness of prevention is still insubstantial, the purpose of dental visit is incorrectly implemented as more for treatment, and rarely for prevention.…”
Section: Logistic Regression Analysesmentioning
confidence: 99%
“…At present, many high-risk factors associated with dental caries have been evidenced, such as poverty, race, eating habits, family economic status, education level, etc. [13][14][15]. However, few studies have separately analyzed and assessed the risk factors for each age group, but instead taken the entire preschool children as a whole, which hindered us from preventing dental caries more effectively through the way of optimizing and enriching OHE.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many high-risk factors associated with dental caries have been demonstrated, such as poverty, race, eating habits, family economic status, education level, etc. [10][11][12]. However, few studies have separately analysed and assessed the risk factors for each age group; instead, they have considered all preschool children as a whole, which has hindered us from preventing dental caries more effectively by optimizing and enriching OHE.…”
Section: Introductionmentioning
confidence: 99%